Creating learning outcomes from threshold concepts for information literacy instruction. Issue 1 (2nd January 2017) - Hosier, Allison
ABSTRACT: Threshold concepts and learning outcomes represent two different ways of thinking about teaching and learning. Finding a way to translate between the two is necessary for librarians who may wish to use concepts from the Framework for Information Literacy to shape their instruction. The following article outlines a process for transforming concepts from the "Scholarship as Conversation" frame into learning outcomes that the author developed as part of a tutorial project. This process can easily be adapted to a variety of instructional situations.